Terapi Kneading Massage dan Teknik Breathing Exercise Diapragmatic (BED) dalam Mengurangi Intensitas Nyeri dan Kecemasan Persalinan - Leli Srirahayu; Surtiningsih Surtiningsih; Linda Yanti (SEHATI: Jurnal Kesehatan, 2024)
Childbirth is a physiological event experienced by some women. The birth process has uncomfortable effects including pain and anxiety. The aim of this research is Kneading Massage Therapy and Diaphragmatic Breathing Exercise (BED) Techniques to Reduce the Intensity of Labor Pain and Anxiety. The method used is a case study with pre-test post-test treatment. The population, namely all mothers giving birth at the Mandiraja 2 Community Health Center in December 2023, was 25 respondents. The sample used was 5 maternal respondents who experienced pain and anxiety using the Accidental Sampling technique. The results obtained after administering Kneading Massage Therapy and Diaphragmatic Breathing Exercise Technique (BED) showed a decrease in the pain scale from before therapy of 5.6 (moderate pain) to around 2.6 (mild pain) after therapy and a decrease in anxiety scale from 40 .4 (moderate anxiety) before therapy to 29.9 (low anxiety) after therapy. So it can be concluded that Kneading Massage Therapy and the Diaphragmatic Breathing Exercise (BED) technique can reduce the intensity of pain and anxiety childbirth.